EVALUATION OF THE STATE OF THE STRESS IN PROFESSIONALS OF THE STRATEGY HEALTH OF THE FAMILY (Fiep Bulletin - online, 2011)
This research if characterizes as a study of field of the descriptive type, with the objective to evaluate the level of stress of the professionals of the health, of the Unit of Health of Family (USF) Aponia, located in the City of Porto Velho, State of Rondonia. The sample was formed by 22 professionals, who worked in the morning period, in the USF Aponia. The data had been collected from the test of level of stress described for OLIVEIRA (2003). It was verified that 72.73% of the professionals had presented a state of stress negative, being that 27.27% of the sample were with state of stress indicative of positive welfare. It was considered necessity of strategies of care with the health of the professionals who act in the Strategy Health of Family (ESF), especially as for the mental health.
Keywords: Strategy Health Family; stress; Professionals of Health